Reflection on Professionalism: Retrospective Review of Health Professional Student Reflections - Parsa, Betsabeh; Murphy, Sue; Drynan, Donna; Jarus, Tal (International Journal of Practice-based Learning in Health and Social Care, 2021)
Professionalism is one of the core competencies for occupational and physical therapists. However, difficulty in providing clear definitions of core professional values and behaviours makes professionalism a complex concept to teach. Most proposed frameworks for defining the concept are theoretical or have focused on the academics’ and clinicians’ perspectives; evidence from students’ experiences is lacking. The purpose of this study was to develop a framework to define the concept of professionalism from occupational therapy (OT) and physical therapy (PT) students’ perspectives through analysis of their reflections. The study was a retrospective content analysis of OT and PT students’ reflections completed during clinical placements from 2014-2015 academic years. Sixty students (30 PT and 30 OT) were randomly sampled and one anonymized reflection of each of these students was selected. The qualitative content analysis was initiated by applying a deductive approach using previously presented frameworks to define professionalism. Four themes emerged which resulted in a new framework to define professionalism from students’ perspectives. The emergent themes included the effect of context, the relational dimension, personal dimension, and societal dimension. Students considered context an overarching factor influencing all dimensions of professionalism. Although their perceptions of professionalism were comparable to other presented frameworks, they primarily focused on the relational and personal dimensions of professionalism. The results of this study indicate that OT and PT students consider professionalism as a multi-dimensional and context-specific concept. Despite understanding contextual barriers, at this stage of their professional identity development, students tried to adhere to ethics, and professional values and responsibilities.